Poultry by-product meal in the diet of broiler chicks - Azman, M. Ali; Dalkilic, B. (Indian Veterinary Journal, 2006)
Poultry by-product meal (PBM) was investigated in broiler chicks as a nutrient since scanty reports are available on the subject.